ANALISIS PEMASARAN BAWANG MERAH DI DESA PANDUNG BATU KECAMATAN BARAKA KABUPATEN ENREKANG - Firda Ayu Hasmir; Iranita Haryono; Aksal Mursalat; Muhammad Rais Rahmat Razak (Institute of Computer Science (IOCS), 2023)
This study aims to find out how the marketing channel, business income and marketing margins of shallots in Pandung Batu Village, Baraka District, Enrekang Regency. The type of research used is descriptive qualitative. The population used in this study were shallot farmers with a total of 3 respondents, collectors 1 respondent, retailers 1 respondent and wholesalers 1 respondent. Data collection was carried out using primary data, namely by interview, observation, documentation, literature study and questionnaire techniques. Secondary data collection was obtained from various sources such as the Central Bureau of Statistics (BPO), books, reports and journals. The results showed that there were 2 types of marketing channels in Pandung Batu Village, Baraka District, Enrekang Regency, namely the first channel from farmers to retailers and then to consumers and the second marketing channel, namely from farmers to collectors then to wholesalers then to retailers and then to consumers. The shallot farming income with a land area of ??1.5 hectares is IDR 306,552,000.00. The income of shallot farming with a land area of ??1 Ha is IDR 161,968,667.00. And the income of shallot farming with a land area of ??0.5 Ha is IDR 305,968,000.00. Marketing channel 1 margin is IDR 8000/Kg and marketing channel 2 margin is IDR 3000/Kg.